Reaproveitamento de resíduos agroindustriais de frutas obtidos por meio de manejo convencional e orgânico: estudo de métodos para a extração verde e sustentável de compostos bioativos - Segatto, Mateus Lodi (Universidade Federal de São Carlos, 2022)
The magnitude of the Brazilian agricultural and agro industrial market impresses by its greatness, but it is also the cause of serious concerns regarding the amount of waste generated and how to handle such residues. This kind of material comprises several chemically-interesting fractions, some of which potentially carrying bioactive compounds that could add value to the process when extracted, integrating biomass-based chemical platforms (biorefineries) when allied to other products and processes. Notably, organic agricultural systems could be interesting feedstocks for biorefineries, as they are not only considered greener production models, but also because they are often linked to a higher presence of flavonoids and other secondary metabolites that have bioactive properties. The central objective of this work is to extract, through green methods, the main bioactive compounds from the processing waste of fruits from both conventional and organic agricultural systems produced in the state of São Paulo, Brazil. Chemometric tools were used on experimental design and data assessment to evaluate and optimize different green extraction methods. Considering mango (Mangifera indica) processing waste, Homogenizer-Assisted Extraction (HAE), Microwave-Assisted Extraction (MAE) and Matrix Solid Phase Dispersion (MSPD) were studied, tested and optimized using ethanol-water (ethanolic) mixtures as solvents and assessing the extraction yield of mangiferin and hyperoside as responses. The use of aqueous solutions of Ionic Liquids (ILs) was also tested and discussed as viable solvent alternatives. Regarding guava (Psidium guajava) processing waste samples, the study was focused on improving the extraction yield of quercetin and vanillin with acidic ethanolic solutions (HCl), using HAE and Ultrasound-Assisted Extraction (UAE) techniques. Besides that, as a proof-of-concept, the use of Hansen Solubility Parameters (HSP) was assessed as a tool for the screening of solvents and mixtures of solvents that allow a higher extraction yield of hesperidin from orange peels (Citrus sinensis). All extracts were analyzed using liquid chromatography and the compounds were quantified using calibration curves obtained with commercially available analytical standards. Response Surface Methodology (RSM) was employed for the assessment of the parameters that affect each extraction technique, as well as the optimization of these variables in terms of the extraction yield. Lastly, biological activity assays were conducted to evaluate the potential use of the ethanolic extracts from mango and guava processing wastes as biocidal products. Mango extracts and mangiferin and hyperoside standards were tested against the microalgae Raphidocelis subcapitata, while both mango and guava extracts were assessed for their insecticidal activity against larvae of Helicoverpa armigera moth and nymphs of the neotropical brown stink bug (Euschistus heros). In order to assess the selectivity of the extracts as a pesticidal product, phytotoxic assays were conducted on soybean plants (Glycine max).
Reuse of agro-industrial fruit processing residues from conventional and organic agriculture: a study of green and sustainable extraction of bioactive compounds
Keywords: Química verde; Química sustentável; Extração de produtos naturais; Quimiometria; Química analítica; Superfície de resposta; Parâmetros de Hansen; Manga; Goiaba; Laranja; Resíduos agroindustriais; Preparo de amostras; Green chemistry; Sustainable chemistry; Extraction of natural products; Chemometrics; Analytical chemistry; Sample preparation; Response surface methodology; Hansen parameters; Mango; Guava; Orange; Agroindustrial waste; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::SEPARACAO; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA